N–TiO2-coated polyester filters for visible light—Photocatalytic removal of gaseous toluene under static and dynamic flow conditions - Zhang, Li (2016)
The present work aims to utilize N-TiO2 coating for decontamination of gaseous pollutants under normal room light irradiation. N-TiO2 nanoparticles were prepared by incomplete thermal oxidation of TiN at different temperatures to achieve self-doping of TiO2 to improve simultaneously the structural, morphological, and electronic properties of conventional TiO2 photocatalyst. The thermal evolution of TiN to oxygen-rich titanium oxynitride (N-TiO2) and subsequently TiO2 at different temperatures is characterized systematically by different tools including XRD, TEM, XPS, UV–vis diffuse reflectance and SPV responses. The synthesized N-TiO2 was coated onto polyester filters using a facile spray coating method. The excellent photocatalytic performance was successfully demonstrated on mineralization of gaseous toluene with fluorescent light irradiation under both static and dynamic flow conditions in a comprehensive custom-built photocatalytic test system. Therefore, it shows promising potential to be utilized in practical air purification applications.